Exploration Behaviors, Body Representations, and Simulation Processes for the Development of Cognition in Artificial Agents - Schillaci, Guido; Hafner, Verena V.; Lara, Bruno (Frontiers in Robotics and AI, 2016)
Sensorimotor control and learning are fundamental prerequisites for cognitive development in humans and animals. Evidence from behavioral sciences and neuroscience suggests that motor and brain development are strongly intertwined with the experiential process of exploration, where internal body representations are formed and maintained over time. In order to guide our movements, our brain must hold an internal model of our body and constantly monitor its configuration state. How can sensorimotor control enable the development of more complex cognitive and motor capabilities? Although a clear answer has still not been found for this question, several studies suggest that processes of mental simulation of action–perception loops are likely to be executed in our brain and are dependent on internal body representations. Therefore, the capability to re-enact sensorimotor experience might represent a key mechanism behind the implementation of higher cognitive capabilities, such as behavior recognition, arbitration and imitation, sense of agency, and self–other distinction. This work is mainly addressed to researchers in autonomous motor and mental development for artificial agents. In particular, it aims at gathering the latest developments in the studies on exploration behaviors, internal body representations, and processes of sensorimotor simulations. Relevant studies in human and animal sciences are discussed and a parallel to similar investigations in robotics is presented.